2020
DOI: 10.2754/avb202089010003
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base balance parameters of follicular fluid and venous blood in cattle

Abstract: The study aimed to compare differences of physiological acid-base balance (ABB) parameters in follicular fluid (FF) and venous blood (VB) and to evaluate ABB parameters in FF collected from different ovarian follicles in dairy cows and heifers. The ABB parameters (pH, pCO2, pO2, HCO3– and base excess (BE)) in the FF of the preovulatory follicle, of the dominant follicle on the 9th day of the cycle and of the superovulatory estrous follicles were compared to VB. Similarly, the dynamics of the ABB profile in FF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Similar to electrolytes and total proteins, acid-base parameters and gases in bovine FF and blood have also been reported by many studies in samples of different days of the estrous cycle or in follicles of different developmental stages 12,22,23,[33][34][35] . However, no report to date has specifically characterized blood and FF parameters while oocytes undergo maturation.…”
Section: Tissue Fluid Gases and Acid-base Parameterssupporting
confidence: 67%
See 3 more Smart Citations
“…Similar to electrolytes and total proteins, acid-base parameters and gases in bovine FF and blood have also been reported by many studies in samples of different days of the estrous cycle or in follicles of different developmental stages 12,22,23,[33][34][35] . However, no report to date has specifically characterized blood and FF parameters while oocytes undergo maturation.…”
Section: Tissue Fluid Gases and Acid-base Parameterssupporting
confidence: 67%
“…Here we found that during this unique window, blood parameters were well-maintained, yet FF underwent significant changes include pH, pCO2, and TCO2. Although Indrova et al 12 collected FF at different times post PG or superovulation, these were conducted in three different experiments, and no comparisons could be made. Additionally, many studies used OPU for FF collection, which increased pO2 due to the mixing of FF with air in the OPU tubing 34,36,37 .…”
Section: Tissue Fluid Gases and Acid-base Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the literature does not describe the collection of follicular fluid to assess the acid-base balance from live animals. Maintaining the acid-base balance in body fluids is essential for maintaining whole-body homeostasis, and many deviations indicate disorders [ 113 ]. Female fertility disorders are correlated with electrolyte concentration [ 66 ].…”
Section: Reproductive Consequences Resulting From Disturbances In Ele...mentioning
confidence: 99%